Strengthening Students’ Character through Islamic Religious Education - Ikhwanul Abrori (AT-TAKILLAH : Jurnal Pendidikan dan Keislaman, 2026)
This study aims to analyze the role of Islamic Religious Education in strengthening students’ character in schools. Character education has become an important issue in modern education because many students are influenced by negative behaviors such as dishonesty, lack of discipline, bullying, and low social awareness. Islamic Religious Education is expected to help students develop positive moral values, ethical awareness, and responsible behavior in their daily lives. This research employed a quantitative approach using a survey research design. The population of this study consisted of students at a selected school, while the sample was determined using purposive sampling techniques. Data were collected through questionnaires, observations, and documentation. The questionnaire used a Likert scale to measure students’ perceptions regarding Islamic Religious Education learning and character strengthening. The collected data were analyzed using descriptive statistics and simple linear regression analysis. The findings revealed that Islamic Religious Education has a positive and significant influence on strengthening students’ character. Students who actively participated in religious learning activities demonstrated better honesty, discipline, responsibility, tolerance, and respect toward others. Teachers, school environments, and religious activities also contributed significantly to students’ moral development. However, several challenges such as low learning motivation, monotonous teaching methods, and negative environmental influences were still identified. Therefore, schools are encouraged to improve the quality of Islamic Religious Education learning through innovative teaching methods, technology integration, and collaboration among teachers, parents, and communities. Overall, this study concludes that Islamic Religious Education plays an essential role in developing students with strong moral values and positive social behavior.